Regulacija in percepcija sovražnega govora - Milosavljevič, Marko (Teorija in praksa, 2012)
The article analyses the way hate speech is interpreted by editors as key gatekeepers and definers of the editorial policy of certain media. Related to this is the question of how hate speech is defined in regulatory and self-regulatory terms and documents. The analysis is based on two methods: first an analysis of key documents that form the framework of Slovenian media and, second, in-depth interviews with editors of selected Slovenian (online) media. We found that certain editors do not differentiate between hate speech and defamatory speech and other forms of controversial or banned speech. These perceptions reveal a lack of knowledge regarding the legal framework of hate speech. The analysis also shows that editors of Slovenian online media donot have a precise regulatory and self-regulatory system and thus many decisions regarding hate speech are arbitrary
Keywords: Journalism; Novinarstvo; Sovražni govor; Hate speech; Regulacija; Regulation; Spletni portali; Web portals; Analiza vsebine; Content analysis (Communication); Slovenia; Slovenija; mass media; množični mediji